Analysis of Spatial Variability of Air Pollutants in a Rural Area - Maciej GLINIAK; Krzysztof GÓRKA; Klaudia TUREK (Communications of International Proceedings, 2021)
Many factors contribute to the formation of air residues, for which rude, transport or home furnaces. Monitoring air quality in Poland allows for the determination of the quality level. The aim of the paper is to assess and analyze the level of seasonal variability of air content for a selected study. Maps have been developed, levels of assigned areas in urban and rural areas in terms of seasons have been discovered. The air quality was compared with the standards regulated by the regulations. Air pollutants with suspended dust PM10 and sulfur dioxide SO2 are characterized by seasonal variability. As a result of the analysis of the analysis of these levels, the shortage did not exceed the moderate level, the scope of which is defined by the regulations.
Keywords: Exploitation; air quality; air flow modeling